PERBANDINGAN BIAYA DAN WAKTU PADA PELAKSANAAN PEKERJAAN KONSTRUKSI DENGAN BETON KONVENSIONAL DAN FLY SLAB (Studi Kasus Proyek Pembangunan Gedung Politeknik Madiun) - Indah Purwaningsih; Kunil Murtachiyatin; Pranoto Samto Admojo; M Agung Wibowo (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The method of construction determines the cost and the time required to complete a construction, as well as quality, safety and health (K3) and the environment produced at the end of the project. This study aims to analyze the cost and time required to complete a storey building, specially a floor plate using a fly slab concrete and compared with the conventional reinforced concrete. Analyz quality, K3 and environment produced from the use of fly slab concrete and compared with the conventional reinforced concrete. The method of this tudy is by re-calculate of the cost and time in construction of Polytechnic Building Madiun which was changed from using the conventional reinforced concrete into the concrete fly slab. The cost recalculation is done by recalculate both the unit volume and price. While the time will be recalculated using Microsoft Project. Quality analysis is done by reviewing the existing concrete quality in the Work Plan and requirement, then compared with the quality of the fly slab concrete. K3 and environmental analysis done by reviewing the application of the K3 and the environment at the project location then compared between the conventional reinforced concrete slab with fly slab concrete. Based on the analysis of the magnitude of the reduction of the cost of implementing development work Polytechnic Building Madiun using fly slab concrete is Rp. 16.740.000,00 or 3 % of the floor plate work using the conventional reinforced concrete. Execution time savings by using fly slab concrete is 12 days or 29 % of the total concrete work timefor second and third floor using the conventional reinforced concrete.The using of fly slab concrete does not reduce the quality of the concrete slab due to the quality of the fly slab concrete that used is higher than the conventional reinforced concrete quality. The using of fly slab concrete can to minimize the work accidents, beside that, the using of fly slab concrete can reduce the wood as formwork and casting the rest of the waste reduction project.